Efektifitas Pelayanan Penjualan Tiket Penyeberangan Dari Bangsal Menuju Tiga Gili - Mardiah Mardiah; Baiq Rienelda; Emi Juniati (JIAP (Jurnal Ilmu Administrasi Publik), 2018)
This study aims to determine the effectiveness of crossing ticket sales services from Bangsal to three Gili and to find out what factors hinder the service from Bangsal to the three Gilis. The problems in this study are (a) how the effectiveness of crossing ticket sales services from Ward to three Gilis and (b) any factors that hinder the service of ticket sales attacks from Bangsal to three Gili. The method used in this study is a qualitative research method with observation techniques, interview techniques and documentation techniques. Data in this study were obtained from primary data, namely data obtained directly from the object of research and secondary data, namely data obtained indirectly. Data collection through these two sources to obtain data on effectiveness and service inhibiting factors. The results of this study can be concluded that the effectiveness of crossing ticket sales service from Ward to three Gilis has been said to be quite effective as seen from public service supporting indicators, namely reliability, tangibles, responsiveness and assurance.